Planting and harvesting innovation: An analysis of Samsung Electronics - Seung Hoon Jang; Sang M. Lee; Taewan Kim; Donghyun Choi (International Journal of Quality Innovation, 2020)
This study explores how firms manage the entire life cycle of innovation projects based on the framework of harvesting and planting innovation. While harvesting innovation seeks new products in the expectation of financial performance in the short term, planting innovation pursues creating value over a long time period. Without proper management of the process of planting and harvesting innovation, firms with limited resources may not be successful in launching innovative new products to seize a momentum in high tech industries. To examine this issue, the case of Samsung Electronics (SE), now an electronics giant originated from a former developing country, is analyzed. SE has shown to effectively utilize co-innovation to maintain numerous planting and harvesting innovation projects. Both researchers and practitioners would be interested in learning about how SE shared risks of innovation investment with external partners at the early stage of innovation cycles.
Keywords: 650; Planting innovation; Harvesting innovation; Co-innovation; Multinationals; Case analysis